The influence of structure depth on image blurring of micrometres-thick specimens in MeV transmission electron imaging. (April 2016) - Wang, Fang; Sun, Ying; Cao, Meng; Nishi, Ryuji
Highlights: Evolution of image blurring of thick specimens with structure depth is presented. Image blurring increases with the decrease of structure depth. Higher electron energy of 2 MeV should be preferred for the reduction of blurring. Multiple elastic scattering below focused structures has obvious effect on blurring. Abstract: This study investigates the influence of structure depth on image blurring of micrometres-thick films by experiment and simulation with a conventional transmission electron microscope (TEM). First, ultra-high-voltage electron microscope (ultra-HVEM) images of nanometer gold particles embedded in thick epoxy-resin films were acquired in the experiment and compared with simulated images. Then, variations of image blurring of gold particles at different depths were evaluated by calculating the particle diameter. The results showed that with a decrease in depth, image blurring increased. This depth-related property was more apparent for thicker specimens. Fortunately, larger particle depth involves less image blurring, even for a 10-μm-thick epoxy-resin film. The quality dependence on depth of a 3D reconstruction of particle structures in thick specimens was revealed by electron tomography. The evolution of image blurring with structure depth is determined mainly by multiple elastic scattering effects. Thick specimens of heavier materials produced more blurring due to a larger lateral spread of electrons after scattering from the structure. Nevertheless, increasing electron energy to 2 MeV can reduce blurring and produce an acceptable image quality for thick specimens in the TEM.